Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1038/pr.2014.26
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, sedentary time, and liver enzymes in adolescents: the HELENA study

Abstract: Background:To examine the association between physical activity (PA) and liver enzyme levels in adolescents from nine European countries. Methods: The study comprised 718 adolescents (397 girls). PA was measured by accelerometry and expressed as total PA (counts/min), and time (min/d) engaged in moderate to vigorous intensity PA (MVPA). Time spent sedentary was also objectively measured. We measured serum levels of alanine aspartate aminostrasferase (AST), alanine aminostransferase (ALT), and γ-glutamyltrasnfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 45 publications
3
14
3
Order By: Relevance
“…AST is abundant in muscle cells, and studies have reported greater physical activity, particularly vigorous activity, to be associated with higher circulating levels possibly because of muscle cell breakdown (39)(40)(41). Consistent with this and our findings, a recent cross-sectional study found that adolescents achieving daily recommended time spent in objectively measured MVPA (compared with those not achieving this recommendation) had lower GGT and ALT but higher AST (42).…”
Section: Discussionsupporting
confidence: 90%
“…AST is abundant in muscle cells, and studies have reported greater physical activity, particularly vigorous activity, to be associated with higher circulating levels possibly because of muscle cell breakdown (39)(40)(41). Consistent with this and our findings, a recent cross-sectional study found that adolescents achieving daily recommended time spent in objectively measured MVPA (compared with those not achieving this recommendation) had lower GGT and ALT but higher AST (42).…”
Section: Discussionsupporting
confidence: 90%
“…Two studies investigated associations between the total volume of sedentary behaviour and liver enzymes (Table S16). The study of Ruiz et al was classified as low ROB and found no significant associations between overall sedentary behaviour and liver enzymes among 12‐ to 18‐year‐old adolescents ( n = 718). In contrast, another study that was not classified as low ROB and that did not adjust for MVPA found that total sedentary time was detrimentally associated with liver enzymes in 7‐ to 15‐year‐olds .…”
Section: Resultsmentioning
confidence: 93%
“…1 Sedentary behaviour, in contrast, affects negatively cardiovascular risk factors 2 and represents 23% of the deaths related to chronic diseases. 1 Sedentary behaviour, in contrast, affects negatively cardiovascular risk factors 2 and represents 23% of the deaths related to chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of physical activity are shown on several health outcomes, such as cardiovascular disease (CVD) and mortality for all causes. 1 Sedentary behaviour, in contrast, affects negatively cardiovascular risk factors 2 and represents 23% of the deaths related to chronic diseases. 3 Being inactive for several years may lead to increased risks for type 2 diabetes (T2D), CVD and premature mortality.…”
Section: Introductionmentioning
confidence: 99%